A Relationship Study of Students' Scores in School Based Oral English Assesment (SBOEA) and English Language Results in Sijil Pelajaran Malaysia (SPM)/ Henry anak Sawi - Sawi, Henry (2011)
This study was to identify the relationship between students' oral proficiency score as measured by the School Based Oral English Assessment (SBOEA) and achievement result of English Language by grade in the Sijil Pelajaran Malaysia (SPM) 1119 English Language Paper. It was also conducted to determine whether Higher English Language Proficiency Students (HELPS) performed equally well on SBOEA and English language in SPM. The model used for the study is a framework based on the work by Bachman and Palmer (1996). The model displays correspondences between communicative language ability, language competence, language use and language performance. The language use tasks were the activities that involved students in using English language in the oral assessment (SBOEA) and in the SPM examination. About 382 Form Five students of SMK Muara Tuang, Kota Samarahan Sarawak were used as subjects for this study and these subjects were those who sat for their SPM examination in 2010. A correlational method and Paired-Samples t-Test were applied in this study in which it tried to find a relationship between scores of students in oral as measured by SBOEA and results of English language in SPM and also the differences on HELPS' scores on SBOEA and English language results. The findings indicated that there were high relationships between students SBOEA's scores and English language results. There were also differences between HELPS scores and English language results. Some pedagogical and methodological suggestions and recommendation were suggested for future studies such as improving techniques and styles on teaching and learning which can affect students' motivation in learning English. The future studies also can focus on results between male and female students and also between science and arts classes. The use of questionnaires and interviews also can be used as research instruments.